Revitalizing a declining historic urban quarter - The Walled City of Famagusta, North Cyprus - Doratli, Naciye; Hoşkara, Şebnem Önal; Vehbi, Beser Oktay; Fasli, Mukaddes (My University, 2007)
Taditional historic urban quarters, which are special places not only due to the cultural heritage they house but also due to their urban pattern, are in danger of losing their traditional character if relevant measures fail to exist and ensure the continuity of this character. The Walled City of Famagusta is a district of the second biggest city of North Cyprus, and like the island as a whole, the Walled City of Famagusta has undergone substantial changes to fit the requirements of the different cultures of its many conquerors. As a spatial reflection of the different socioeconomic lifestyles or attitudes of the rulers - Lusignan (1192-1489), Venetian (1489-1571), Ottoman (1571-1878), British (1878-1960) - the urban pattern, as well as the buildings and their functions, have been modified through time. Consequently, the historic areas have become places of intermingling cultures. The Walled City of Famagusta, as many other historic quarters elsewhere in the world, is in a process of decay and deterioration, and its functionally distinctive areas are severely threatened by physical, functional, locational, and image obsolescence at varying degrees. Considering revitalization of the Walled City in a long-term perspective, this diversity should be taken into account for successful decision-making. The aim of this paper is to propose conservation and revitalization measures to address the deterioration and obsolescence process of the Walled City, in Northern Cyprus, based on a thorough study at both architectural and urban levels. SWOT analysis method, which has been used for the purpose of this paper, is based on a field and questionnaire survey and has conveyed an understanding of the environmental and sociocultural qualities. Copyright © 2007, Locke Science Publishing Company, Inc. Chicago, IL, USA. All Rights Reserved.
Keywords: building; cultural heritage; heritage conservation; lifestyle; urban history; urban housing; urban planning; Asia; Cyprus; Eurasia; Famagusta [Cyprus]; Middle East